2010
DOI: 10.1126/science.1183090
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Behavioral Profiling Links Drugs to Biological Targets and Rest/Wake Regulation

Abstract: A major obstacle for the discovery of psychoactive drugs is the inability to predict how small molecules will alter complex behaviors. We report the development and application of a highthroughput, quantitative screen for drugs that alter the behavior of larval zebrafish. We found that the multi-dimensional nature of observed phenotypes enabled the hierarchical clustering of molecules according to shared behaviors. Behavioral profiling revealed conserved functions of psychotropic molecules and predicted the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
683
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 697 publications
(700 citation statements)
references
References 20 publications
15
683
0
2
Order By: Relevance
“…For instance, serotonergic nuclei are densely innervated by hypocretin immunoreactive neurons (Kaslin et al 2004;Panula et al 2010). Detailed behavioral studies revealed conservation between fish and mammalian responses to pharmacological agents that promote or antagonize sleep (Rihel et al 2010;Sigurgeirsson et al 2011).…”
Section: Fish Sleepmentioning
confidence: 99%
“…For instance, serotonergic nuclei are densely innervated by hypocretin immunoreactive neurons (Kaslin et al 2004;Panula et al 2010). Detailed behavioral studies revealed conservation between fish and mammalian responses to pharmacological agents that promote or antagonize sleep (Rihel et al 2010;Sigurgeirsson et al 2011).…”
Section: Fish Sleepmentioning
confidence: 99%
“…They hatch from their chorions by 2-3 days post fertilization (dpf), develop fully functioning organs by 4-5 dpf, and exhibit a large number of behaviors by 7 dpf 5,6 . Zebrafish larvae are ideally suited for high-throughput analyses because of their small size 7,8 . Software is commercially available for automated analyses of behavior in larval and adult zebrafish [9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…In signature-based approaches, a series of drug-induced molecular/phenotypic measurements are made in an experimental system. Collections of measurements from many small molecules form multivariate signatures that aim to fingerprint drugs based on their relative signature similarity (8)(9)(10)(11)(12)(13). In several landmark studies using Saccharomyces cerevisiae; gene expression compendia (8); and, later, barcoded loss of function/ORF libraries (9,10), large signatures were shown to characterize individual small molecule mechanisms of action effectively.…”
mentioning
confidence: 99%